Functional and structural analysis of BPSS0140-BPSS0142 ABC transporter that mediates fructose import in Burkholderia pseudomallei - Shu, Sian How; Su, Datt Lam; Sheila Nathan,; Chieng, Sylvia (Penerbit Universiti Kebangsaan Malaysia, 2022)
ATP-binding cassette (ABC) transporters mediate bacteria uptake or export of a variety of solutes across biological membranes. Bacterial uptake of the monosaccharides is important as a source of carbohydrate building blocks that contribute to the bacteria’s major structure. Burkholderia pseudomallei is the etiological agent of melioidosis and within its genome, 33 genes related to monosaccharide ABC transporters have been predicted. The presence of these transporters is believed to assist in bacterial survival and adaptation in various environments. Despite a large number of genes in the genome, most of these systems have yet to be characterized, including the bpss0140-bpss0142 operon. Here, we predicted the 3D structure of each protein encoded by bpss0140-0142 and identified the specifically associated monosaccharides. In silico analyses of the structures demonstrated that BPSS0140 is a sugar-binding protein, BPSS0141 is a transmembrane permease and BPSS0142 is an ATPase. Through protein structure modeling and protein-ligand docking, several specific monosaccharide sugars were found to interact with the BPSS0140-BPSS0142 ABC transporter. To validate the in silico prediction, knock-out mutants for each of the genes were constructed. A growth profile between wild-type and mutants in an M9 medium supplemented with glucose, fructose, ribose, and galactose as predicted from the protein-ligand docking was then performed. The growth of mutants decreased significantly compared to the wild-type bacteria when grown in M9 supplemented with fructose as the sole carbon source indicating that this transporter is potentially the main fructose transporter in B. pseudomallei.